Endoscopic Ultrasound-Guided Fine-Needle Biopsy for Pancreatic Lesions is the Way Forward: Here is the Evidence! - Jha, Daya Krishna; Rana, Surinder Singh (Journal of Digestive Endoscopy, 2022)
Endoscopic ultrasound-guided tissue acquisition (EUS TA) has increasingly become imperative for pancreatic pathology in arriving at the correct diagnosis because of its simplicity, cost-effectiveness, and availability at high-volume centers. The advent of EUS fine-needle biopsy (FNB) has revolutionized EUS TA by providing samples that are larger and more diagnostic compared with fine-needle aspiration (FNA). Rapid onsite evaluation (ROSE) has been conventionally used for improving the cytological yield as well as diagnostic accuracy of EUS FNA. The development of FNB has obviated the need for ROSE, and evidence from retrospective and comparative studies has suggested that FNB is as good as FNA with ROSE in terms of diagnostic accuracy and reduced costs. However, strong evidence in the form of a randomized controlled trial (RCT) was missing. In this news and views, we discuss a multicenter RCT that has compared the diagnostic accuracy of EUS FNB alone to EUS FNA with ROSE in patients with solid pancreatic lesions. This study has reemphasized that EUS FNB has a diagnostic accuracy comparable to EUS + ROSE at a comparable cost and requires fewer passes and has a shorter procedure time.
Keywords: endosonography; fine-needle biopsy; fine-needle aspiration